N6-Methyladenosine RNA Methylation in Cardiovascular Diseases - Liu, Chi; Gu, Lei; Deng, Wenjuan; Meng, Qianchao; Li, Nan; Dai, Guifeng; Yu, Suli; Fang, Hong (Frontiers in Cardiovascular Medicine, 2022)
N6‑methyladenosine (m6A) modification is the most universal and abundant post-transcriptional modification of eukaryotic RNA and occurs mainly at the consensus motif RR(m6A)CH (R=A or G, H=A, C, or U) in long internal exons, near stop codons, or in the 3’ untranslated region (UTR). “Writers”, “erasers”, and “readers” are responsible for the occurrence, removal, and recognition of m6A modification, respectively. Substantial evidence has shown that m6A RNA modifictaion can exert important functions in physiological and pathological processes. Cardiovascular diseases (CVDs) are a wide array of disorders affecting heart or vessels, including atherosclerosis (AS), hypertension (HT), ischemia/reperfusion (I/R) injury, myocardial infarction (MI), stroke, cardiac hypertrophy, heart failure (HF), and so on. Despite the advances in lipid-lowering drugs, antihypertensives, antiplatelet agents, and anticoagulation therapy, CVDs are still the leading cause of death worldwide. Recent studies have suggested that m6A modification of RNA may contribute to the pathogenesis of CVDs, providing a novel research insight for CVDs. Herein, we provide an up-of-date summarization of the molecular mechanism of m6A and the roles of m6A in different types of CVDs. At last, we propose that m6A might be a potential biomarker or therapeutic target for CVDs.